Cost, Tariffs, And Electricity Pricing In Iran: A Comparative Study - Mirzakuchaki, Sattar; Vaziri, Navid (Metallurgical and Materials Engineering, 2024)
In recent years, the design and implementation of electricity tariff mechanisms have become crucial for ensuring a sustainable supply, promoting consumption efficiency, and advancing social justice, serving as key tools in energy policy. In both developed and developing countries, industrial electricity prices are generally lower than residential prices to support production activities and maintain competitive commercial consumption. However, contrary to this global trend, the average ratio of industrial to residential electricity prices in Iran has increased in recent years, signaling a structural imbalance in the tariff system and support policies. Under the tiered pricing system, lower consumption levels are charged at cheaper rates, providing incentives for low-consuming groups. However, the segmentation of consumption and the determination of thresholds in Iran, particularly in tropical regions, require a thorough and equitable review. According to the 2020 tariff, in regular areas, the first tier (0–100 kWh), which offers the lowest rate, covers only about 25% of subscribers, while in Tropical Area 3, the first tier (0–1000 kWh) covers more than 93% of subscribers, resulting in a substantial subsidy for this group. This disproportionate subsidy has escalated to the point where, out of a total of 200 billion tomans in electricity subsidies during a hot month, more than 190 billion tomans (93%) is allocated to the first tier. Consequently, even with a significant increase in rates for higher tiers, it is impossible to fully eliminate subsidies for this region, and the financial imbalance in the electricity sector remains unresolved. The objective of this comparative study is to examine the electricity tariff structures in Iran in relation to international standards, identify key challenges in defining consumption ranges and thresholds, and propose solutions to enhance economic efficiency, social justice, and transparency in the pricing process. The findings of this analysis could serve as a foundation for policymakers and regulatory bodies to reform the tariff tiers, adjust subsidies appropriately, and implement effective incentive rates, thereby ensuring both the financial sustainability of the grid and the promotion of optimized consumption and industrial production support.